Predictive Control of Speed, Steering, and Braking For an Autonomous Car on Uphill and Downhill Road - Aditya, Ryan; Santoso, Ari (ULTIMA Computing, 2025)
Countries around the world have roads that go through mountains and hills. These roads can have features such as winding and change of elevation. When passing through such roads, the car’s dynamics are influenced by the unknown elevations and curvatures, which can threaten stability if not properly controlled. The purpose of this research is to control the cars longitudinal speed through acceleration, braking through regenerative braking and maintain lateral control through steering inputs. The proposed control system consists of a high-level predictive controller which predicts the car’s dynamics under varying road condition and a low-level Fuzzy-PID controller for the actuators, which is motor driver and electric power steering. Additionally, the energy recovery from the regenerative braking system is monitored to evaluate its impact on battery state of charge, especially when the car is slowing down or going through downhill roads. The control system proposed aims to maintain speed and steering stability under varying road conditions and improve energy efficiency.